2005
DOI: 10.1073/pnas.0507170102
|View full text |Cite
|
Sign up to set email alerts
|

A chemosensory system that regulates biofilm formation through modulation of cyclic diguanylate levels

Abstract: Pseudomonas aeruginosa causes chronic biofilm infections, and its ability to attach to surfaces and other cells is important for biofilm formation and maintenance. Mutations in a gene called wspF, part of a putative chemosensory signal-transduction operon, have been shown to result in cell aggregation and altered colony morphology. The WspF phenotypes depend on the presence of WspR, which is a member of a family of signal transduction proteins known as response regulators. It is likely that the effect of the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
958
3
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 732 publications
(1,013 citation statements)
references
References 50 publications
(53 reference statements)
28
958
3
9
Order By: Relevance
“…WspR is part of the Wsp chemosensory signal transduction system, which operates to produce c-di-GMP as its effector output function. The Wsp system is homologous to chemotaxis systems and includes a membrane-bound receptor protein, WspA, and a response regulator GGDEF protein, WspR, that catalyzes c-di-GMP synthesis when phosphorylated and upon contact with surfaces (61). In addition to controlling the adhesiveness of P. aeruginosa upon surface contact, WspR is also linked to regulation of the chaperone usher pathway (cup) genes that encode putative fimbrial adhesins.…”
Section: Modulation Of Cyclic Di-gmpmentioning
confidence: 99%
See 2 more Smart Citations
“…WspR is part of the Wsp chemosensory signal transduction system, which operates to produce c-di-GMP as its effector output function. The Wsp system is homologous to chemotaxis systems and includes a membrane-bound receptor protein, WspA, and a response regulator GGDEF protein, WspR, that catalyzes c-di-GMP synthesis when phosphorylated and upon contact with surfaces (61). In addition to controlling the adhesiveness of P. aeruginosa upon surface contact, WspR is also linked to regulation of the chaperone usher pathway (cup) genes that encode putative fimbrial adhesins.…”
Section: Modulation Of Cyclic Di-gmpmentioning
confidence: 99%
“…Mutations in a gene called wspF, part of the Wsp chemosensory signal-transduction operon, have been shown to result in cell aggregation and altered colony morphology, a phenotype which correlated with increased cellular levels of c-di-GMP and increased biofilm formation. Transcriptomic analysis suggested that the wspF mutant phenotype can be attributed to increased expression of the pel and psl operons, which were among at least 560 genes with affected expression in this strain (61). Expression of a protein predicted to catalyze degradation of c-di-GMP (e.g., PvrR) reversed the phenotype of a ⌬wspF mutant and inhibited biofilm initiation by wild-type cells, indicating that the presence of c-di-GMP is necessary for biofilm formation (42,61).…”
Section: Modulation Of Cyclic Di-gmpmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the biological pathways through which c-di-GMP regulates persistence, cell aggregation and the switch to the commensal lifestyle are currently poorly understood, the proteins responsible for c-di-GMP synthesis and degradation have been determined and, at least partially, characterized. Bacterial diguanylate cyclase (DGC) activity is found in GGDEF domain-containing proteins (Paul et al, 2004;Ryjenkov et al, 2005;Hickman et al, 2005;Kulesekara et al, 2006), whilst EAL domain-containing proteins have been shown to have c-di-GMP-specific phosphodiesterase (PDE) activity (Bobrov et al, 2005;Christen et al, 2005;Schmidt et al, 2005;Kulesekara et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, PleD controls the onset of motility during the C. crescentus cell cycle (Aldridge et al, 2003;Paul et al, 2004). In Pseudomonas aeruginosa, autoaggregation is controlled by the GGDEF response regulator WspR (D'Argenio et al, 2002;Hickman et al, 2005), and twitching motility by FimX, which contains GGDEF and EAL domains (Huang et al, 2003;Kazmierczak et al, 2006). Additional examples of the effects of GGDEF domains on cell attachment and motility include ScrC regulation of attachment factors in Vibrio parahaemolyticus (Boles & McCarter, 2002), control of curli fimbriae by AdrA in S. typhimurium (Simm et al, 2004), and RocS effects on V. cholerae motility (Rashid et al, 2003).…”
Section: Introductionmentioning
confidence: 99%